2008
DOI: 10.1007/s10863-008-9173-7
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on Peter Mitchell and the chemiosmotic theory

Abstract: In 1991 Peter Mitchell wrote a last article that summarised his views on the origin, development and current status of his chemiosmotic ideas. I here review some of his views of that time on structures and mechanisms of several key bioenergetic components in relation to the subsequent advances that have been made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…It has been said that:'.. (Mitchell's) experimental and conceptual work proved extraordinarily successful in providing proof of the general hypothesis and prompting mechanisms of key components..'. 4 It is worth pointing out that the model proposed here does not conflict with Mitchell's theory. Rather, it reveals the still unrecognized potential of Mitchell's theory, also in being extendable to the emerging awareness of extramitochondrial OXPHOS.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It has been said that:'.. (Mitchell's) experimental and conceptual work proved extraordinarily successful in providing proof of the general hypothesis and prompting mechanisms of key components..'. 4 It is worth pointing out that the model proposed here does not conflict with Mitchell's theory. Rather, it reveals the still unrecognized potential of Mitchell's theory, also in being extendable to the emerging awareness of extramitochondrial OXPHOS.…”
Section: Discussionmentioning
confidence: 49%
“…The topic of H þ cycling, pivotal in oxidative phosphorylation, is central in energy conversion. 3,4 Mitchell's chemiosmotic theory foresaw the existence of an H þ translocation by the ETC, coupled to the transfer of electrons to oxygen with the formation of water, being the energy involved in the process in the form of H þ flux, converted to ATP by F o F 1 -ATP synthase nanomotor. 3 H þ was also pivotal for the origin of life.…”
Section: Introductionmentioning
confidence: 99%
“…First, the mitochondrial dysfunction theory of insulin resistance implies that mitochondrial content and/or capacity dictates resting rates of fat oxidation. However, this prediction goes against the widely accepted chemiosmotic model of respiration [75], which holds that absolute rates of fuel oxidation under aerobic conditions depend ultimately on ATP turnover (i.e., workload). A high work rate increases the intramitochondrial ADP/ATP ratio, which promotes proton influx from the inner mitochondrial space through ATP synthase.…”
Section: Mitochondrial Dysfunction: Cause or Consequence Of Metabomentioning
confidence: 92%
“…The octanol/water partition coefficients of methyl and ethylmercury are 1.4 to 1.8 [21, 23], at intracellular pH and [Cl − ], thus both organomercury compounds will predominately exist as lipophilic cations inside cells. Mitchell demonstrated that lipophilic cations accumulate inside mitochondria, in a Nernstian fashion, driven by the steady state membrane potential [24]. Given that the typical mitochondrial membrane potential of astrocytes and neurons is between 140–170 mV [25], one would, a prior , expect the concentration of these organomercury compounds within mitochondria to be approximately 1000 times greater than the cytosolic concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The damage of a cell's mitochondria leads to the activation of the apoptotic cascade and subsequent cell death [3, 4, 24, 2631]. This may be clinically relevant in the setting of a patient who harbors a known or unknown mitochondrial disorder.…”
Section: Introductionmentioning
confidence: 99%